Maximum–norm a posteriori error estimates for an optimal control problem - Otárola, Enrique; Rankin, Richard; Salgado, Abner J. (Springer, 2019)
We analyze a reliable and efficient max-norm a posteriori error estimator for a control-constrained, linear–quadratic optimal control problem. The estimator yields optimal experimental rates of convergence within an adaptive loop. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.